Answer:
The absolute difference is:
If we find the % of change respect the before case we have this:
So then is a big change.
Step-by-step explanation:
The subindex B is for the before case and the subindex A is for the after case
Before case (with 500)
For this case we have the following dataset:
500 200 250 275 300
We can calculate the mean with the following formula:
And the sample deviation with the following formula:
After case (With -500 instead of 500)
For this case we have the following dataset:
-500 200 250 275 300
We can calculate the mean with the following formula:
And the sample deviation with the following formula:
And as we can see we have a significant change between the two values for the two cases.
The absolute difference is:
If we find the % of change respect the before case we have this:
So then is a big change.
Answer:
x = 5
Step-by-step explanation:
Add the equations
x + y = 3
x - y = 7
––––––––
2x = 10
Divide both sides by2
x = 5
Note: for the equations in the question,
none of the given answers are correct.
(2, 7) are the coordinate which ordered pair is a solution to the following system of inequalities and .
<h3>What is inequality?</h3>
Inequality is defined as the relation which makes a non-equal comparison between two given functions.
we want to find which ordered pair is a solution to the following system of inequalities.
The solution of a inequality is the ordered pair that is a solution to all inequalities in the system and the graph of the inequality is the graph of all solutions of the system.
Graph one line at the time in the same coordinate plane and shade the half-plane that satisfies the inequality.
x = 2 and y = 7
Learn more about inequality ;
brainly.com/question/14164153
#SPJ1
Answer:
C
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
y - 5 = - 3(x + 2) ← is in point- slope form
with slope m = - 3
Given a line with slope m then the slope of a line perpendicular to it is
= - = - =
and (a, b) = (6, - 1), hence
y - (- 1) = (x - 6), that is
y + 1 = (x - 6) → C